Specifications for Textbook Materials at Madrasah Ibtidaiyah - Suwardi Suwardi; Burhan Yusuf Habibi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2022)
This study aims to find the specification of textbook material for grade 1 Madrasah Ibtidaiyah (MI) in Salatiga City. This study used descriptive qualitative and descriptive quantitative approaches. A qualitative descriptive approach was employed to describe the data obtained through the interview method, with the type of guided interview. The interview method used an interview guide instrument, analyzed through the stages of analyzing data, reducing data, categorizing data, interpreting data, and drawing conclusions. Meanwhile, a quantitative descriptive approach was utilized to describe the data obtained through a questionnaire, which used a filling type questionnaire. Questionnaire data were then analyzed using descriptive statistical formulas. The study results found that the material specifications for the MI grade 1 textbook in Salatiga City had been adjusted to the core competencies (KI) and basic competencies (KD) set by the government; the development of the material was sourced from information technology that can be accounted for and from similar books; the material was adapted to the students' abilities; the material was adapted to the conditions of the student's cultural environment; the material paid attention to the condition of student diversity; the material contains factual truths and concepts; supporting learning; the material begins with question and command sentences. The theoretical implication of this finding is that it can be used as a reference in assessing and developing textbooks at MI.